Indonesia’s Tax Performance and Dividend Tax Reform Policy: From Self to Official Assessment System - Efendi Ibnususilo (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
Tax law reform in Indonesia aims to establish a simple, fair, and legally certain tax system within a self-assessment framework. One strategic aspect of this reform is dividend taxation, which lies at the intersection of state fiscal interests, economic neutrality, and investment competitiveness. This study analyzes Indonesia’s tax policy and the evolution of dividend tax reform through three main focuses the normative foundation and development of national tax policy strengthening the self-assessment system under the law on harmonization of tax regulations, the transformation of dividend taxation from a classical system to a single-tier approach with conditional exemptions; and implementation challenges related to legal certainty, regulatory structure, and taxpayer compliance culture. The research applies statute, conceptual, and comparative law approaches. The findings show that: first, strengthening self-assessment under HPP Law improves administrative efficiency but still faces challenges in tax literacy and normative consistency; second, dividend tax reform reduces the risk of double taxation but has not fully achieved normative simplification due to reliance on technical regulations; and third, regulatory fragmentation and the absence of certain statutory definitions create legal uncertainty that may affect compliance and system effectiveness. Accordingly, the study highlights the need for coherent normative reconstruction to enhance legal certainty, tax neutrality, and fiscal legitimacy in supporting national economic stability.